2018
DOI: 10.1136/bjophthalmol-2018-312967
|View full text |Cite
|
Sign up to set email alerts
|

Combination of multimodal imaging features predictive of choroidal nevus transformation into melanoma

Abstract: AimTo characterise combinations of multimodal imaging risk factors and predictive value for choroidal nevus transformation into melanoma.MethodsThis is a retrospective review of multimodal imaging features for 3806 choroidal nevi from 1 January 2007 through 1 January 2017. Kaplan-Meier estimates and Cox regression analyses were used to calculate 5-year percentages of growth to melanoma and HR.ResultsUsing multimodal imaging, six risk factors predictive of choroidal nevus transformation into melanoma were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…Low internal acoustic reflectivity (i.e., ‘ultrasonographic hollowness’) can aid the differentiation of choroidal nevi from melanomas [ 25 , 33 , 34 ] and is helpful in a sub-specialty ocular oncology practice when weighing the risks and benefits of treatment versus observation. With respect to echographic changes over time, Doro et al found that nevi < 1.5 mm thick showed no change, whereas a progressive increase in hollowness on B-scan occurred in 18% of tumors with thickness > 1.5 mm [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low internal acoustic reflectivity (i.e., ‘ultrasonographic hollowness’) can aid the differentiation of choroidal nevi from melanomas [ 25 , 33 , 34 ] and is helpful in a sub-specialty ocular oncology practice when weighing the risks and benefits of treatment versus observation. With respect to echographic changes over time, Doro et al found that nevi < 1.5 mm thick showed no change, whereas a progressive increase in hollowness on B-scan occurred in 18% of tumors with thickness > 1.5 mm [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the presence of various combinations of the risk factors for future growth are the basis for counselling and treatment decisions [15], their role in determining the urgency of referrals to an ocular oncologist has not been studied. There will be fears that the MOLES scoring system will delay the treatment of some patients with choroidal melanoma, because the likelihood of malignancy is underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…The overall mean 5‐year estimates for transformation were 1% for those with no risk factor, 11% with one factor, 22% with two factors, 34% with three factors, 51% with four factors and 55% with five risk factors 3 . A further report identified that not all risk factors inferred the same risk for growth, with the highest hazard ratio with each combination of factors always including symptoms of visual acuity loss and orange pigment 4 . Furthermore, the risk of growth into melanoma increased with each millimetre increase in naevus thickness, emphasizing the importance of lesion thickness when monitoring pigmented uveal lesions 5 .…”
Section: Uveal Melanoma Size and The Detection Of Small Uveal Melanommentioning
confidence: 95%